Hey there! Sign in to join this conversationNew here? Join for free
    • Thread Starter
    Offline

    0
    ReputationRep:
    Hey folks I was wondering if someone can check these revision questions and see if they are correct please. thanks

    1. Use the factor theorem to factorise completely f(x)= x³+x²-4x-4.
    Hence solve the equation x³+x²-4x-4=0

    x³+x²-4x-4=0
    x² (x + 1) - 4(x + 1) = 0
    (x + 2)(x + 1)(x - 2) = 0
    x = -2 , -1 , 2

    Remainder theorum questions
    2. Determine the remainder when x³-6x²+x-5 is divided by:
    a. X+2

    f(x) = x³ - 6x² + x - 5
    f(-2) = (-2)³ - 6(-2)² + (-2) - 5
    -8 - 24 - 2 - 5 = -39

    b. X-3

    f(x)= x³ - 6x² + x-5
    f(3)³ - 6(3)² + (3) - 5
    27-54+3-5= -29

    Is my remainder theorum correct now?

    As for factor theorum I am lost.
    • Study Helper
    Online

    13
    Study Helper
    (Original post by sunny1982)
    Hey folks I was wondering if someone can check these revision questions and see if they are correct please. thanks

    1. Use the factor theorem to factorise completely f(x)= x³+x²-4x-4.
    Hence solve the equation x³+x²-4x-4=0

    x³+x²-4x-4=0
    x² (x + 1) - 4(x + 1) = 0
    (x + 2)(x + 1)(x - 2) = 0
    x = -2 , -1 , 2
    Where'e the use of the factor theorem?

    Remainder theorum questions
    2. Determine the remainder when x³-6x²+x-5 is divided by:
    a. X+2

    f(x) = x³ - 6x² + x - 5
    (x+2)= f(-2) = (-2)³ - 6(-2)² + (-2) - 5
    -8 - 24 - 2 - 5 = -39

    b. X-3

    f(x)= x³ - 6x² + x-5
    (x-3)=f(3)³ - 6(3)² + (3) - 5
    27-72+3-5= -43
    6 times 9 = ?
    • Thread Starter
    Offline

    0
    ReputationRep:
    (Original post by ghostwalker)
    Where'e the use of the factor theorem?



    6 times 9 = 54 ?
    is it meant to 54 instead of 72?

    What do you mean I haven't used the factor theorum?
    • Study Helper
    Online

    13
    Study Helper
    (Original post by sunny1982)
    is it meant to 54 instead of 72?
    Yep.

    What do you mean I haven't used the factor theorum?
    Well you've clearly factorised the expression, but you've not used the factor theorem to do it. You jumped straight to the second part of the question and factorised f(x)=0 - which admittedly is easier to do in this situation.

    Factor theorem says if f(a)=0 then f(x)=(x-a)g(x)
    • Thread Starter
    Offline

    0
    ReputationRep:
    (Original post by ghostwalker)
    Yep.



    Well you've clearly factorised the expression, but you've not used the factor theorem to do it. You jumped straight to the second part of the question and factorised f(x)=0 - which admittedly is easier to do in this situation.

    Factor theorem says if f(a)=0 then f(x)=(x-a)g(x)
    So is my remainder theorem questions correct apart from the 54 obviously?lol


    So which bit of the equation have I missed out on the factor theorum?
    Offline

    1
    ReputationRep:
    Firstly find some value of 'a' for which f(a) = 0. Then take a factor of (x - a) from f(x), leaving g(x), then factorise the quadratic g(x).
    • Study Helper
    Online

    13
    Study Helper
    (Original post by sunny1982)
    So is my remainder theorem questions correct apart from the 54 obviously?lol
    Essentially.

    (x+2)= f(-2) = (-2)³ - 6(-2)² + (-2) - 5

    The bit in bold however doesn't make sense.

    You could say "remainder on division by (x+2) is f(-2) = ...", of just "remainder is f(-2) = ..." since it's clear from the context what you're dividing by.

    But (x+2) does not equal f(-2)

    So which bit of the equation have I missed out on the factor theorum?
    The start.

    Initially you had f(x) =x³+x²-4x-4.

    Then checking you find f(-1) = 0.

    Hence f(x)=(x+1)g(x) and work out what g is.

    And repeat for g(x).

    It's not the easiest way to do it. And your method would probably be the best way to go about it if they hadn't said "Use the factor theorem".

    This seems more an exercise in getting used to using the factor theorem, rather than just solving a polynomial.
    • Thread Starter
    Offline

    0
    ReputationRep:
    (Original post by Joshmeid)
    Firstly find some value of 'a' for which f(a) = 0. Then take a factor of (x - a) from f(x), leaving g(x), then factorise the quadratic g(x).
    How?
    I haven't got this in my notes
    Offline

    0
    ReputationRep:
    The factor theorem states if for some quadratric f(x), f(a)=0

    Then (x-a) is a factor of f(x)

    For your quadratic, show that f(1)=0
    • Thread Starter
    Offline

    0
    ReputationRep:
    Remainder theorum questions
    2. Determine the remainder when x³-6x²+x-5 is divided by:
    a. X+2

    f(x) = x³ - 6x² + x - 5
    f(-2) = (-2)³ - 6(-2)² + (-2) - 5
    -8 - 24 - 2 - 5 = -39

    b. X-3

    f(x)= x³ - 6x² + x-5
    f(3)³ - 6(3)² + (3) - 5
    27-54+3-5= -29

    Is my remainder theorum correct now?

    As for factor theorum I am lost.

    1. Use the factor theorem to factorise completely f(x)= x³+x²-4x-4.
    Hence solve the equation x³+x²-4x-4=0

    x³+x²-4x-4=0
    x² (x + 1) - 4(x + 1) = 0
    (x + 2)(x + 1)(x - 2) = 0
    x = -2 , -1 , 2

    How many expressions am I missing and inbetween which line?
    • Study Helper
    Online

    13
    Study Helper
    (Original post by sunny1982)
    Remainder theorum questions
    2. Determine the remainder when x³-6x²+x-5 is divided by:
    a. X+2

    f(x) = x³ - 6x² + x - 5
    f(-2) = (-2)³ - 6(-2)² + (-2) - 5
    -8 - 24 - 2 - 5 = -39

    b. X-3

    f(x)= x³ - 6x² + x-5
    f(3)=3³ - 6(3)² + (3) - 5
    27-54+3-5= -29

    Is my remainder theorum correct now?
    Corrected the typo. Yes, that's fine.

    As for factor theorum I am lost.

    1. Use the factor theorem to factorise completely f(x)= x³+x²-4x-4.
    Hence solve the equation x³+x²-4x-4=0

    x³+x²-4x-4=0
    x² (x + 1) - 4(x + 1) = 0
    (x + 2)(x + 1)(x - 2) = 0
    x = -2 , -1 , 2

    How many expressions am I missing and inbetween which line?
    It's the methodology.

    By the factor theorem you show f(x)=(x + 2)(x + 1)(x - 2)

    I'd suggest checking your textbook or Googling if you don't have any notes on the factor theorem.

    THEN (this is the hence part of the question)

    If f(x) = 0,
    then (x + 2)(x + 1)(x - 2)=0

    And so x = -2, or -1 or 2.
    • Thread Starter
    Offline

    0
    ReputationRep:
    f(x) = x³ + x² - 4x - 4

    f(x) = (x³ + x²) - (4x + 4)

    f(x) = x²(x + 1) - 4(x + 1)

    f(x) = (x + 1)(x² - 4)

    f(x) = (x + 1)(x² - 2²)

    f(x) = (x + 1)(x + 2)(x - 2)

    x³ + x² - 4x - 4 = 0

    (x + 1)(x + 2)(x - 2) = 0

    I went a away and I've tried to factorise this completely using Factor theorum so I was wondering if this is correct or is there still some work need doing to it got an exam coming up
    • Study Helper
    Online

    13
    Study Helper
    (Original post by sunny1982)
    ...
    you've done similar to what you did in your first post. You've not used the factor theorem.

    Have a look at this video. It's not too long.
 
 
 
  • See more of what you like on The Student Room

    You can personalise what you see on TSR. Tell us a little about yourself to get started.

  • Poll
    What's your favourite Christmas sweets?
    Useful resources

    Make your revision easier

    Maths

    Maths Forum posting guidelines

    Not sure where to post? Read the updated guidelines here

    Equations

    How to use LaTex

    Writing equations the easy way

    Student revising

    Study habits of A* students

    Top tips from students who have already aced their exams

    Study Planner

    Create your own Study Planner

    Never miss a deadline again

    Polling station sign

    Thinking about a maths degree?

    Chat with other maths applicants

    Can you help? Study help unanswered threads

    Groups associated with this forum:

    View associated groups
  • See more of what you like on The Student Room

    You can personalise what you see on TSR. Tell us a little about yourself to get started.

  • The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

    Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

    Quick reply
    Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.